2020
DOI: 10.1556/022.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Ecological Knowledge and the Cultural Significance of Plants in Hungarian Communities in Slovenia

Abstract: Traditional ecological knowledge of plants is an important aspect of scholarship in relation to land use and contributes to the sustainable use and management of natural resources as well as to the monitoring of changes in the natural environment. The aim of the present paper was to examine traditional ecological knowledge in Hungarian communities in Slovenia in connection with knowledge of the plants growing in the region, their local names, and their uses. We quantified the earlier role of the utilized plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…We interviewed local residents, especially practicing and retired farmers, who were considered to be knowledgeable about the local fauna. We contacted our interviewees partly based on earlier ethnobiological works (Babai et al, 2021;, and to a lesser extent through snowball sampling. The average age of the interviewees was 75 (53-92) in in Hungary.…”
Section: Methods Of Data Collectionmentioning
confidence: 99%
“…We interviewed local residents, especially practicing and retired farmers, who were considered to be knowledgeable about the local fauna. We contacted our interviewees partly based on earlier ethnobiological works (Babai et al, 2021;, and to a lesser extent through snowball sampling. The average age of the interviewees was 75 (53-92) in in Hungary.…”
Section: Methods Of Data Collectionmentioning
confidence: 99%
“…A decreased abundance of wild plants was observed by several authors [69,102,110,111], frequently attributed to changing climate [79,88,90] or the disappearance of the place of growth following ecosystem changes [56,93,96,112,113]. Some elderly informants reported that landscape changes such as forest expansion and decreased coppices or agricultural intensification are among the anthropogenic land-use changes responsible for this reduction [58,107,109,114], and others blame the practice of intensive mowing [90,113] as well as the increased use of chemical products as responsible [57,83]. Similarly, some informants noted that the disappearance of sheep herding resulted in a decreased abundance of wild plants [69].…”
Section: Environmental Reasonsmentioning
confidence: 98%